Impact of the surgical approach for neoadjuvantly treated gastroesophageal junction type II tumors: a multinational, high-volume center retrospective cohort analysis - Wirsik, Naita Maren; Schmidt, Thomas; Nienhüser, Henrik; Donlon, Noel E.; de Jongh, Cas; Uzun, Eren; Fuchs, Hans F.; Brunner, Stefanie; Alakus, Hakan; Hölscher, Arnulf H.; Grimminger, Peter; Schneider, Martin; et al. (Annals of surgery, 2023)
Objective: The aim of this study was to explore oncologic outcomes of transhiatal gastrectomy (THG) or transthoracic esophagectomy (TTE) for neoadjuvantly treated gastroesophageal junction (GEJ) Siewert type II adenocarcinomas, a multinational, high-volume center cohort analysis was undertaken. Background: Neoadjuvant radiochemotherapy or perioperative chemotherapy (CTx) followed by surgery is the standard therapy for locally advanced GEJ. However, the optimal surgical approach for type II GEJ tumors remains unclear, as the decision is mainly based on individual experience and assessment of operative risk. Methods: A retrospective analysis of 5 prospectively maintained databases was conducted. Between 2012 and 2021, 800 patients fulfilled inclusion criteria for type II GEJ tumors and neoadjuvant radiochemotherapy or CTx. The primary endpoint was median overall survival (mOS). Propensity score matching was performed to minimize selection bias. Results: Patients undergoing THG (n=163, 20.4%) had higher American Society of Anesthesiologists (ASA) classification and cT stage (P<0.001) than patients undergoing TTE (n=637, 79.6%). Neoadjuvant therapy was different as the THG group were mainly undergoing CTx (87.1%, P<0.001). The TTE group showed higher tumor regression (P=0.009), lower ypT/ypM categories (both P<0.001), higher nodal yield (P=0.009) and higher R0 resection rate (P=0.001). The mOS after TTE was longer (78.0 vs 40.0 months, P=0.013). After propensity score matching a higher R0 resection rate (P=0.004) and mOS benefit after TTE remained (P=0.04). Subgroup analyses of patients without distant metastasis (P=0.037) and patients only after neoadjuvant chemotherapy (P=0.021) confirmed the survival benefit of TTE. TTE was an independent predictor of longer survival. Conclusion: Awaiting results of the randomized CARDIA trial, TTE should in high-volume centers be considered the preferred approach due to favorable oncologic outcomes.
Gesehen am 06.12.2023